Teacher-student experiences experienced in the university extension community projects subject – Univali - Vieira, Márcia Gilmara Marian (2021)
This article aims to present the experiences of academics in the discipline of Community Project for University Extension (PCEU) at the University of Vale do Itajaí (UNIVALI) incorporating a new concept of the classroom via the elaboration of mini-projects in the context of the pandemic “COVID 19 ”. The project “Education for Transformation: Changing Lives”, established dialogues with the confrontation of contemporary social and economic problems, such as: the inclusion of the population at risk and social vulnerability and search for food security as one of the conditions for the conquest of citizenship in its fullness. In the period from March to June 2020, using the methodology based on the Paulo Freire Culture Circle System, by means of Dialog Circles. The academics, in turn, had the opportunity to socialize their different knowledge exercising their citizenship, and in this process, the development of skills and competences that contribute to their integral formation.